Exploring theatrical form for the political engagement of young people in Wales - Laura Stowe (WISERD Annual Conference 2017, 2017)
Unlike other forms of engagement, theatre has an immediacy which provides its audience with action and involvement. Theatre can be exciting and thought-provoking, but at the same time it provides a safe space to explore complex and challenging ideas. And whilst theatre can certainly be used to tackle the most serious of subjects, it also has the ability to engage in a fun, social, and collaborative way. This makes it an ideal tool for working with young people to explore both political issues and the broader political landscape generally.